2007
DOI: 10.1016/j.jmatprotec.2006.08.025
|View full text |Cite
|
Sign up to set email alerts
|

The use of Taguchi method in the design of plastic injection mould for reducing warpage

Abstract: Plastic injection moulding is one of the most important polymer processing operations in the plastic industry today. However, lack of skill in mould making and injection moulding machine control will lead to defective plastic product. Warpage is one type of defect that usually appears in products with thickness less than 1 mm.This project is going to fabricate a mould that produced a thin plate with dimension 120 mm × 50 mm × 1 mm. The thin plate will be used for warpage testing. In mould fabrication, the moul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(106 citation statements)
references
References 3 publications
1
103
0
2
Order By: Relevance
“…However, this approach cannot ensure optimum conditions due to a lack of evaluating of other factors in their suitable range [51]. Basically, Taguchi method is a considerable approach to remove these obstacles in experiment design [52]. Therefore, similar to our previous studies, Taguchi method was used for achieving optimum conditions based on the selection of three parameters (incubation times, CuSO 4 and glucose concentrations) [25,33,53].…”
Section: Taguchi Designmentioning
confidence: 99%
“…However, this approach cannot ensure optimum conditions due to a lack of evaluating of other factors in their suitable range [51]. Basically, Taguchi method is a considerable approach to remove these obstacles in experiment design [52]. Therefore, similar to our previous studies, Taguchi method was used for achieving optimum conditions based on the selection of three parameters (incubation times, CuSO 4 and glucose concentrations) [25,33,53].…”
Section: Taguchi Designmentioning
confidence: 99%
“…Shen et al (2007) also found that at higher temperatures more shrinkage was produced and at higher pressure of compaction less shrinkage occurred. Tang et al (2007) …”
Section: Analysis Of the Shrinkagementioning
confidence: 99%
“…The above Table highlights the importance of selection of parameters and the significance of their optimum levels to achieve a robust process or parameter design [1][2][3][4][5][6][7][8][9]. The parameters like screw stroke, injection temperature have been found out less important and nozzle temperature has been substituted for barrel temperature.…”
Section: Table No 1 Parameters Considered By Various Authors For Promentioning
confidence: 99%